Neuroprotective maraviroc monotherapy in simian immunodeficiency virus-infected macaques: reduced replicating and latent SIV in the brain - Kelly, Kathleen M. (AIDS, 2013)
OBJECTIVE: HIV-associated neurocognitive deficits remain a challenge despite suppressive combined antiretroviral therapy. Given the association between HIV-induced central nervous system (CNS) disease and replication of HIV in immune-activated macrophages, CCR5 antagonists may attenuate CNS disease by modulating inflammatory signaling and by limiting viral replication. DESIGN: To establish whether initiating CCR5 inhibition during early infection altered CNS disease progression, outcomes were compared between simian immunodeficiency virus (SIV)-infected macaques treated with maraviroc (MVC) versus untreated SIV-infected macaques. METHODS: Six SIV-infected rhesus macaques were treated with MVC monotherapy for 5 months beginning 24 days postinoculation; 22 SIV-infected animals served as untreated controls. SIV RNA levels in plasma, cerobrospinal fluid, and brain, and CNS expression of TNFα and CCL2 were measured by qRT-PCR. Immunostaining for CD68 and amyloid precursor protein in the brain was measured by image analysis. Plasma sCD163 was measured by ELISA. RESULTS: SIV RNA and proviral DNA levels in brain were markedly lower with MVC treatment, demonstrating CCR5 inhibition reduces CNS replication of SIV and may reduce the CNS latent viral reservoir. MVC treatment also lowered monocyte and macrophage activation, represented by CNS CD68 immunostaining and plasma sCD163 levels, and reduced both TNFα and CCL2 RNA expression in brain. Treatment also reduced axonal amyloid precursor protein immunostaining to levels present in uninfected animals, consistent with neuroprotection. CONCLUSION: CCR5 inhibitors may prevent neurologic disorders in HIV-infected individuals by reducing inflammation and by limiting viral replication in the brain. Furthermore, CCR5 inhibitors may reduce the latent viral reservoir in the CNS. Adding CCR5 inhibitors to combined antiretroviral regimens may offer multiple neuroprotective benefits.